Irish Education Policy for a Globalised World: A Policy for Chasing Black & White Swans. - LARKIN, CHARLES; THIJSSEN, JACCO JOHAN JACOB (The Swan Group, 2009)
The record decline of over 9% in Irish GDP in 2009 provides the backdrop to this important study. Government expenditure has grown rapidly in the Celtic Tiger era without much evidence of a value for money culture in any area of public spending. Unsustainable borrowing and tax increases postpone only briefly the need for better appraisals of public policies and spending in Ireland. Education is the first area of public spending to be studied through the generosity of the FBD Trust in this series.
PUBLISHED
Keywords: Education, education policy, innovation, economic growth, regulation